The Internet Based Text Material: Its Impact to Students’ Reading Comprehension on Skimming and Scanning for Information to the Seventh Grade of SMP Wahidiyah - Putri Novitasari (Kirana Publisher (KNPub), 2023)
The objective of this study intended to find out whether there is significance influence of internet based text material to the students’ reading comprehension on scanning and skimming for information to the Seventh Grade of SMP Wahidiyah. In this research text was specified on descriptive text. Descriptive quantitative research was implemented as the research design. The sample of this research was students from 7A at SMP Wahidiyah which consist of 41 students. They were given a pre-test and post-test. The result showed that the mean score before students taught using internet based text material was 68,41 and the score after being taught using internet based text was 93,4. The result of t-score was 17,59 and the t-table was 1,68 at the level of significance was 0,05. Furthermore, from the data it can be seen that the students’ score and their mean score was increased. Related to the hypothesis and the data analization, it can be concluded that the alternative hypothesis (Ha) was accepted and the null hypothesis (H0)was rejected. It means that there was significanct influence of internet based text material to the students’ reading comprehension on scanning and skimming for information to the Seventh Grade of SMP Wahidiyah.